Rotation of Guanine Amino Groups in G-Quadruplexes: A Probe for Local Structure and Ligand Binding - Adrian, Michael (2017)
Nucleic acids are dynamic molecules whose functions may depend on their conformational fluctuations and local motions. In particular, amino groups are dynamic components of nucleic acids that participate in the formation of various secondary structures such as G-quadruplexes. Here, we present a cost-efficient NMR method to quantify the rotational dynamics of guanine amino groups in G-quadruplex nucleic acids. An isolated spectrum of amino protons from a specific tetrad-bound guanine can be extracted from the nuclear Overhauser effect spectroscopy spectrum based on the close proximity between the intra-residue imino and amino protons. We apply the method in different structural contexts of G-quadruplexes and their complexes. Our results highlight the role of stacking and hydrogen-bond interactions in restraining amino-group rotation. The measurement of the rotation rate of individual amino groups could give insight into the dynamic processes occurring at specific locations within G-quadruplex nucleic acids, providing valuable probes for local structure, dynamics, and ligand binding.